New Multiple Solution to the Boussinesq Equation and the Burgers-Like Equation - Hasan Bulut; Münevver Tuz; Tolga Akturk (Journal of Applied Mathematics)
By considering an improved tanh function method, we found some exact solutions of Boussinesq and Burgers-like equations. The main idea of this method is to take full advantage of the Riccati equation which has more new solutions. We found some exact solutions of the Boussinesq equation and the Burgers-like equation.